Process development of roasted talisay (Terminalia catappa) kernels - Langurayan, Lean Angel Diaz (2011.)
The potential economic, nutritional and health values known about talisay has created a research interest on the kernels.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Talisay